A voz de Deus e do Diabo em Viva Cariri - Puccini, Sérgio (Imagofagia, 2021)
This article analyses the modulation of the voice in Geraldo Sarno’s documentary Viva Cariri (1970). The voice over, which shares space with other voices coming from direct sound capture, has a significant presence in Cariri. Rather than following the procedure adopted in Viramundo (1965), marked by the dominance of what Jean-Claude Bernardet defined as the voice of the owner, in Cariri Geraldo Sarno opts for a construction that values discordant relationships, incorporating situations of conflict between the voice of the film-maker and the voices of others.